Quality of life among young people in the Alps - Čataković Biagi, Dijana (Revija za geografijo, 2025)
Measuring quality of life encompasses various dimensions, including individual perceptions and societal values. The Erasmus+ project Alpine Compass focuses on the quality of life for young people in the Alps, comparing their needs and challenges in France, Germany, Liechtenstein, and Slovenia through studies and interviews. This article combines literature analysis with interview opinions to identify new indicators for measuring quality of life. Quality of life is multifaceted, involving material conditions and subjective perceptions. Key results include the importance of a healthy environment, sustainable mobility, cultural offerings, mental health, and the impact of climate change on the future.
Keywords: alpine regions; alpske regije; indicators; Kakovost življenja; kazalniki; life in the Alps; mladi; Mladina; youth; življenje v Alpah